Analysis of mid-spatial frequency wavefront distortions from a liquid-cooled flash-lamp pumped Nd:phosphate laser amplifier - Pierre-Marie Dalbies; Sandy Cavaro; Edouard Bordenave; Nathalie Blanchot; Julien G. Moreau; Jérôme Neauport (High Power Laser Science and Engineering, 2024)
Mid-spatial frequency wavefront deformation can be deleterious for the operation of high-energy laser systems. When fluid cooled high-repetition-rate amplifiers are used, the coolant flow is likely to induce such detrimental mid-spatial frequency wavefront deformations. Here, we describe the design and performance of a 90 mm × 90 mm aperture, liquid-cooled Nd:phosphate split-slab laser amplifier pumped by flash-lamps. The performance of the system is evaluated in terms of wavefront aberration and gain at repetition rates down to 1 shot per minute. The results show that this single cooled split-slab system exhibits low wavefront distortions in the medium to large period range, compatible with a focus on target, and despite the use of liquid coolant traversed by both pump and amplified wavelengths. This makes it a potential candidate for applications in large high-energy laser facilities.